Investigating the Effectiveness of Ecoliteracy-Integrated Project-Based Learning in Fostering Creative Thinking Skills Among Elementary School Students - Chaesar, Ari Suryawati Secio; Andayani (Universitas Muhammadiyah Malang, 2024)
This research was grounded in the issues identified at Tlahap Public Elementary School, Temanggung Regency, namely, students' suboptimal understanding of explanatory text writing, suboptimal mastery of creative thinking skills, and low environmental awareness. This research aimed to explain the effectiveness of the ecoliteracy based project-based learning on creative thinking skills compared to the conventional learning model in elementary school students. The investigation applied a quantitative approach involving an experimental method. Hence, it consisted of experimental and control groups. Employing a random sampling method, Class VA was selected as the experimental group, and class VB was chosen as the control group at Tlahap Public Elementary School, Temanggung Regency. Data collection was conducted via observation, questionnaires, and tests. Instruments were previously tested using the content validity method. Data analysis utilized analysis of variance with a significance level of 5%. Prerequisite tests were conducted before treatment, including a normality distribution test and a homogeneity of variance test. The results indicated normal and homogeneous distribution. Analysis of variance t-test on posttest data of the experimental and control groups showed a probability value of 0.000 (p <0.05). The average posttest score of the experimental class was 85.57, while the control was 77.14. The conclusion is that the project-based learning model based on ecoliteracy and creative thinking skills in explanatory test writing instructions was more effective than the conventional model for elementary school students.